HUBUNGAN KEMATANGAN EMOSI DENGAN KECENDERUNGAN PERILAKU CYBERBULLYING PADA PENGGUNA TWITTER DI UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Sri Gustiningsih; hartosujono hartosujono (Universitas Sarjanawiyata Tamansiswa, 2013)
ABSTRACTThis research aims to determine the relationship between emotional maturity and tendencies of cyberbullying behavior on twitter user. The hypothesis, there is a negative relationship between emotional maturity and cyberbullying behavior tendencies on twitter user. The subjects are students at the University Sarjanawiyata Tamansiswa Under graduated program, 18-24 years old, male and female, and have a twitter account, amounting to 82 people. The measures used tendencies of cyberbullying behavior scale and emotional maturity scale. Data processed using the Product Moment of Pearson technique with the help of statistical program SPSS version 20 for Mac. The results of relationship values obtained relationship between emotional maturity and tendencies of cyberbullying behavior of (r)= -0283 with p = 0.005 (p < 0.05). This shows that the hypothesis shows there is a negative relationship between emotional maturity and tendencies of cyberbullying behavior are acceptable. It means that the higher the emotional maturity of students twitter users then the lower the tendencies of cyberbullying behavior. Conversely the lower the emotional maturity of twitter users, the higher the tendencies of cyberbullying behavior. Key words: Cyberbullying, emotional maturity, twitter users